Influences of Varying Combination of Feed Rate and Depth of Cut to Tool Wear Rate and Surface Roughness: High Speed Machining Technique in Non-High Speed Milling Machine - Mohd Zairulnizam, Mohd Zawawi; Mohd Ali Hanafiah, Shaharudin; Ahmad Rosli, Abdul Manaf (Trans Tech Publications, Switzerland, 2014)
Machining technique using high spindle speed, high feed rate and shallow depth of cut utilize in High Speed Milling (HSM) machines offer several benefits such as increase of productivity, elimination of secondary and semi-finishing process, reduce tool load and small chips produced. By adjusting some of the machining parameters, non-HSM machine having lower spindle speed and feed rate could also take advantages some of the benefits mentioned above when applying the HSM technique. This experiment investigate the effects of varying combination of depth of cut and feed rate to tool wear rate and surface roughness during end milling of Aluminum and P20 tool steel in dry condition. The criterion for tool wear before it gets rejected is based on maximum flank wear, Vb of 0.6mm. Material removal rate, spindle speed and radial depth of cut are constant in this experiment. After preliminary machining trials, the combination starts with depth of cut of 2mm and feed rate of 45mm/min until the smallest depth of cut and highest feed rate of 0.03mm and 3000mm/min respectively. The obtained result shows that for both materials, feed rate significantly influences the surface roughness value while depth of cut does not as the surface roughness value keep increasing with the increase of feed rate and decreasing depth of cut. Whereas, tool wear rate almost remain unchanged indicates that material removal rate strongly contribute the wear rate. With no significant tool wear rate, this study demonstrates that HSM technique is possible to be applied in non-HSM machine with extra benefits of eliminating semi-finishing operation, reducing tool load for finishing, machining without coolant and producing smaller chip for ease of cleaning.